Modification of Mn on corrosion and mechanical behavior of biodegradable Mg88Y4Zn2Li5 alloy with long-period stacking ordered structure. (1st April 2020) - Zhang, Jiaxin; Zhang, Jinshan; Han, Fuyin; Liu, Wei; Zhang, Longlong; Zhao, Rui; Xu, Chunxiang; Dou, Jing
Abstract: The biological corrosion behavior and mechanical properties of Mg89- x Y4 Zn2 Li5 Mn x ( x  = 0, 0.5, 1, 1.5 and 2 at.%) alloy with long-period stacking ordered (LPSO) structure were investigated in this work. The magnesium matrix and the eutectic phase of Mg88 Y4 Zn2 Li5 Mn1 alloy are effectively refined by the grain boundary segregation of Mn, and the average size of matrix and the eutectic phase decreased by 66 % and 74 %, respectively. The ultimate tensile strength (UTS) and elongation enhanced by 36 % and 55 %, respectively. The corrosion rates obtained by weight loss and hydrogen evolution of Mg88 Y4 Zn2 Li5 Mn1 alloy were 79 % and 84 % lower than that of Mg88 Y4 Zn2 Li5 alloy. Additionally, Mg88 Y4 Zn2 Li5 Mn1 alloy also presents superior corrosion behavior in electrochemical test. It is verified that Mn plays a positive role in both corrosion and mechanical properties of the Mg88 Y4 Zn2 Li5 Mn1 alloy, which provides a reference for further experimental work.